A network analysis of body satisfaction of people with gender dysphoria. (June 2016) - van de Grift, T.C.; Cohen-Kettenis, P.T.; Elaut, E.; De Cuypere, G.; Richter-Appelt, H.; Haraldsen, I.R.; Kreukels, B.P.C.
Highlights: Body satisfaction in gender dysphoria can be divided in different body areas. Genital body dissatisfaction is limitedly associated with overall dissatisfaction. Socially visible characteristics influence overall body satisfaction. In trans women, voice and hair are central body characteristics. In trans men, muscularity and posture are central body characteristics. Abstract: In gender dysphoria (GD), much of the experienced distress results from body dissatisfaction. The current study analyzed the configuration of body satisfaction in trans men and women using network analysis. In total, 485 individuals diagnosed with GD from four European countries, applying for medical treatment, filled out the Body Image Scale for Transsexuals. A six-factor model reflecting different body areas was confirmed via confirmatory factor analysis. A further configuration of body satisfaction was modelled using correlation network analysis techniques in R. Genital dissatisfaction showed limited connection with other body areas in comparison to other subscales. Body characteristics influencing social gender recognition were most centrally involved in body (dis)satisfaction in both natal sexes. In trans women these characteristics were related mostly to voice and hair, whereas in trans men these characteristics were related to muscularity and posture. Focusing on these socially influential body characteristics may provide important targets for transgender healthcare.